Analysis of Factors Affecting the Income of Working Women - Misdawita Misdawita; Bunga Chintia Utami (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The condition of poverty experienced by the poor causes the inheritance of poverty between generations. Responding to increasingly high economic conditions and demands, those who play a role in making a living in the household are not only men but also women. Rokan Hilir Regency is the third highest number of poor people in Riau Province, and one of the villages in Rokan Hilir is the coldest village. To help the family economy where the husband's income has not been able to meet family income. Through working women means an increase in income for poor families. This addition is a contribution of women's income that can be used to meet family needs so that family welfare can be achieved. So the purpose of this study is to analyze the factors that affect the income of working women in Tanah Putih District, Rokan Hilir, Riau Province. The method used is the Multiple Linear Regression Method using primary data from 50 samples of women working in Sedinginan Village. The results of this study found that education level, age and husband's income had a positive and significant effect on women's income, while marital status had no significant effect.